Gastrointestinal Complications After Surgical Correction of Neuromuscular Scoliosis: A Retrospective Cohort Study. (September 2018) - Jalanko, T.; Helenius, I.; Pakarinen, M.; Koivusalo, A.
Study Design: A retrospective cohort study of consecutively operated neuromuscular scoliosis patients. Background and Aim: Surgical correction of neuromuscular scoliosis can be complicated by early gastrointestinal complications, but data on the extent and severity of them is scarce. The aim of the study was to determine the incidence, course, and risk factors of gastrointestinal complications after neuromuscular scoliosis correction. Material and Methods: Ninety-one patients (<21 years of age) were consecutively operated on for neuropathic neuromuscular scoliosis during 2000–2011. Patients who developed marked postoperative gastrointestinal complications were identified and clinical, operative, and radiographic records, death certificates, and post-mortem reports were examined. Results: The average age at surgery was 14.5 (SD 2.9) and follow-up time was 4.9 (SD 2.3) years. Gastrointestinal complications occurred in 12 (13%) patients and included prolonged paralytic ileus (7%, 6/91), dysphagia (7%, 6/91), and gastroparesis (1%, 1/91). Hospital stay was 22 (SD 11) days in patients with gastrointestinal complications and 16 (SD 20) days in non-complicated patients (p = 0.005). Dysphagia required permanent feeding gastrostomy in one patient whereas other complications were transient and none caused death. The risk factors for postoperative gastrointestinal complications were preoperative main curve correction <30% in traction/bending radiographs (Relative Risk (RR) = 28 (95% Confidence Interval (CI) 4.4–180); p < 0.001), preoperative main curve >90° (RR = 5.5 (95% CI 1.3–23); p = 0.020), disturbance in intraoperative spinal cord monitoring (RR = 6.0 (95% CI 1.1–34); p = 0.043), and intravenous opioid medication over 5 days postoperatively (RR = 7.9 (95% CI 1.8–35), p = 0.006). Conclusion: Gastrointestinal complications occurred in 13% of patients after neuromuscular scoliosis correction. Marked gastrointestinal complications extended postoperative hospitalization period, but they were transient in majority (92%) of cases and none caused death. Rigid scoliosis was the most significant risk factor for gastrointestinal complications. Gastrointestinal complications appear to be less frequent after posterior only spinal fusion with total pedicle screw instrumentation and Ponte osteotomies.